2013
DOI: 10.1080/13670050.2013.793651
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into CLIL-related sections of EFL coursebooks: issues of CLIL inclusion in the publishing market

Abstract: The current ELT global coursebook market has embraced CLIL as a weak form of bilingual education and an innovative component to include in General English coursebooks for EFL contexts. In this paper I investigate how CLIL is included in ELT coursebooks aimed at teenaged learners, available to teachers in Argentina. My study is based on the content analysis of four series which include a section advertised as CLIL-oriented. Results suggest that such sections are characterised by (1) little correlation between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…However, a recent large-scale CLIL program evaluation in Spain revealed a lack of key egalitarianism or social inclusion principals essential to CLIL education (Cañado 2018). CLIL materials and teaching resources were also criticised for their lack of authenticity and scarce integration of technology (Cañado 2018), highlighting the importance of inclusiveness and authenticity in teaching content knowledge to EFL students (Cañado 2018;Darío 2014).…”
Section: Bridging Literacy and Science Educationmentioning
confidence: 99%
“…However, a recent large-scale CLIL program evaluation in Spain revealed a lack of key egalitarianism or social inclusion principals essential to CLIL education (Cañado 2018). CLIL materials and teaching resources were also criticised for their lack of authenticity and scarce integration of technology (Cañado 2018), highlighting the importance of inclusiveness and authenticity in teaching content knowledge to EFL students (Cañado 2018;Darío 2014).…”
Section: Bridging Literacy and Science Educationmentioning
confidence: 99%
“…As a result, CLIL practitioners may rely heavily on centralised or ready-made materials (Yang, 2020). Currently, CLIL materials are mostly written based on EFL principles to cater to a large international market (Banegas, 2014) and thus customised adaptation and connection to local cultures are rarely detected (Bell & Gower, 2011;Tomlinson, 2012). Furthermore, these TESOL-based CLIL materials tend to overlook the balance of content and language designs (Coyle, Hood, & Marsh, 2010).…”
Section: Designing and Evaluating Clil Materials To Raise Cultural Awmentioning
confidence: 99%
“…Due to the lack of commonly-recognised systems for judging the quality of CLIL materials, sometimes the rules of evaluating EFL books would be used as most of the current materials are often designed in a language-based weak CLIL form. However, these criteria may not be appropriate for the conceptual framework of CLIL pedagogy (Banegas, 2014;Yang, 2018). Several CLIL researchers have attempted to establish the principles of evaluating quality CLIL materials such as Ball, Kelly, and Clegg (2015), Mehisto (2012), and Yang (2018), who used Mehisto's standards to appraise his self-produced CLIL textbook.…”
Section: Designing and Evaluating Clil Materials To Raise Cultural Awmentioning
confidence: 99%
“…Underpinned by the critical analysis by Cenoz et al (2014) and by Dallinger et al (2016), CLIL implementation can be found extensively in Europe, but to a lesser extent in North and South America, Australia, Asia, or Africa, primarily due to a lack of suitable materials. Dario Banegas (2014) found that advertised CLIL-oriented EFL coursebooks have "(1) little correlation between featured subject specific content and school curricula in L1 (non-English), ( 2) oversimplification of contents and (3) dominance of reading skills development and lower-order thinking tasks" (p. 345). Ball et al (2015) consider that many materials have no consideration of language or culture support because they are not produced for EFL learners.…”
Section: Cultural Factorsmentioning
confidence: 99%